Associations of serum carotenoids with the severity of sunburn and the risk of cancer: A cross-sectional analysis of 1999–2018 NHANES data - Cheng, Bin; Wu, Xixin; Li, Ruina; Tu, Jiayuan; Lin, Sixian; Zhang, Xiangda; Mo, Xiaoqiao; Xie, Tian (Frontiers in Nutrition, 2022)
Background: Sunburn is a common problem for outdoor workers and casual outdoor walkers. Carotenoids are important elements in normal function of skin tissue and skin metabolism and are critical in the development of some cancers. However, the possible relationships between sunburn sensitivity, carotenoids and the risk of cancers remain unknown. Objectives: To explore the associations of serum carotenoids with sunburn severity and the risk of cancers. Methods: A cross-sectional study from the National Health and Nutrition Examination Survey from 1999–2018 were conducted. The relationship between sunburn and serum carotenoids, cancers were investigated by unconditional or ordinal logistic regression. Mediation analysis was used to explore the effect of carotenoids on the relationship between sunburn and cancers. Results: A total of 25,440 US adults from 1999–2018 were enrolled in this study. There were significant differences in sex, race and natural hair colour between the sunburn and nonsunburn people. The severity of sunburn was significantly associated with serum trans-b-carotene, cis-b-carotene, combined Lutein and vitamin A. The odds ratios of severe reactions were 5.065 (95% CI: 2.266~11.318) in melanoma patients, 5.776 (95% CI: 3.362~9.922) in nonmelanoma patients, and 1.880 (95% CI: 1.484~2.380) in nonskin cancers patients. Additionally, serum carotenoids were partially attributable to the effect of sunburn on skin and nonskin cancers. Conclusions: Sunburn severity was associated with cancers, and severer sunburn was related with higher risk of cancers. Serum carotenoids were also associated with sunburn severity. Moreover, the relationship between sunburn and cancers was mediated by some serum carotenoids.